Fiscal policy, price stabilization and incomplete markets - Venegas Martínez, Francisco (Estudios Económicos de El Colegio de México, 2005)
This paper develops a stochastic model of temporary stabilization of prices with the exchange rate acting as a nominal anchor of inflation. The model presents imperfect credibility, and explicitly recognizes the uncertainty in the dynamics of the exchange rate and in the expected behavior of fiscal policy. It is assumed that a mixed diffusion-jump stochastic process drives the exchange rate. Also, the model supposes that the tax rate on wealth follows a geometric Brownian motion. Under this framework, it is assumed that a derivatives market to hedge against future devaluation does not exist, that is, financial markets are incomplete. Consumption and portfolio decisions of a representative consumer, in equilibrium, are examined when the stabilization plan is implemented and fiscal policy is uncertain. Finally, the effects of exogenous shocks in the exchange-rate policy and economic welfare are assessed.